Springate Analysis in Measuring Financial Distress on Company Performance in The Property and Real Estate Sector Listed on The Indonesia Stock Exchange Period 2018 - 2022 - Herdyan, Dwiki; Khalifah, Alif Mohamad; Irfan Ibrahim, Master; Sunardi, Nardi (Journal of Applied Business, Taxation and Economics Research, 2024)
This research aims to determine the effect of financial distress on company performance in the property and real estate sector listed on the Indonesia Stock Exchange for the 2018-2022 period, which is measured using the Springate analysis method. The performance of the property sector has been greatly impacted by the Covid-19 pandemic. Along with paralyzed economic activity, especially in 2020, the performance of the property sector was also paralyzed. Financial distress is a situation where a company experiences financial difficulties. Financial difficulties if they continue can result in the company going bankrupt. Financial distress can be considered an early warning of the company's poor condition so that the company can prepare itself to face this and improve its financial condition and improve company performance. Measurement of the financial distress variable uses the Springate Method